Design and development of planar wideband patch antenna for UHF RFID tag - Mohd Saiful Riza bin Bashri (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
Radio Frequency Identification (RFID) technology utilizing Ultra-high Frequency (UHF) band has become significantly popular due to ever growing use in various sectors such as supply chain management, animal and human tracking, automatic access, automatic toll collection and healthcare goods monitoring which can be attributed to long read range, high transmission data rate and large storage capacity. Basic components of UHF RFID system consists of a reader and a tag where tag is made up of a microchip and an antenna. A passive tag operates in the absence of its on board power source or battery. Hence it depends intensely on the antenna to harvest the energy from the transmitting electromagnetic wave emitted by enquiring reader. Typically, tag antenna is designed as modified printed dipole antenna. However, this type of antenna suffers severe performance degradation when mounted on metallic object. As a result, several methods have been proposed to mitigate the problem such as by separating the printed dipole antenna from the metallic surface using foam spacer or the use of grounded type antenna such as Inverted-F antenna (IFA), planar Inverted-F antenna (PIFA) or microstrip patch antenna. Most of the proposed microstrip patch antennas have narrow bandwidth which limits its operation to certain region or country. Moreover, its complex structure that uses of via hole and shorting wall or plate would increase the fabrication cost. Two different types of wideband planar patch antenna for UHF RFID tag have been designed, simulated and fabricated to overcome the limits of the existing patch antenna. Unlike typical microstrip antenna, impedances of the proposed antennas are complex conjugate matched with the reference microchip impedance ( = 31 − 212 Ω) by using an inductively coupled loop structure. For impedance bandwidth enhancement, a multi planar resonator technique has been used to excite two and three resonance frequencies close to each other to form a wide impedance bandwidth between155 MHz (return loss≤−3 dB) and 117 MHz (return loss≤−6 dB). Simulation and parametric refinement have been done by using FEM based electromagnetic simulator, Ansoft HFSS v13. The overall sizes of the antennas are 87 mm x 45 mm x 1.6 mm and 130 mm × 63 mm × 1.6 mm respectively. The simulated and measured complex impedances of the antennas show a good agreement. The radiation pattern of the prototype antennas have been measured in an anechoic chamber and then compared with the simulated results which also show a good agreement and they are well matched. The maximum gains of the antennas are −7.2 dBi and −5.5 dBi respectively. These results suggest that the UHF RFID tag with proposed antennas can be useful for large metallic object such as metal containers where it can be shipped all over the world.